Determination of goal pose for accurate parking of nonholonomic robots - Ng, Zhihong (2018)
As technology has become more advanced, engineers are able to design an autonomous robot that could deal with various kinds of hectic work environment problems. Autonomous robots regularly have advanced highlights, for example, the machine learnings that can assist them in understanding their physical condition and mechanize parts of their support and heading that used to be executed by human hands.